EFEITO DE FUNGOS CONTAMINANTES NA PRODUTIVIDADE DE DOIS ISOLADOS DE AGARICUS BLAZEI EM DUAS FORMULAÇÕES DE COMPOSTO - Andrade, M.c.n. De [UNESP]; Minhoni, M.t.a. [UNESP]; Zied, D.c. [UNESP]; Sales-campos, C.; Kopytowski, J (Instituto Biológico, 2020)
The effect of the contaminant fungi Trichoderma sp. and Chaetomium olivacearum on the cultivation of the ABL 99/30 and ABL 04/49 isolates of A. blazei in two compost formulations made up with tyfton (Cynodom dactylon) and oat (Avena sativa) was evaluated. The experimental design was a totally randomized 2 x 2 x 3 factorial design with 6 repetitions. The experimental unit consisted of 12-12.5 kg of wet compost. During the spawning, 150 g of Trichoderma sp. and C. olivacearum were added to the compost. The experiment was carried out in a climatized room, with humidity between 75-90% and temperature of 28º C. The productivity averages of the ABL 99/30 isolate of A. blazei were higher than those of ABL 04/49 and Trichoderma sp. and C. olivacearum negatively influenced the production of A. blazei. The different composts (based on tyfton and oat straw) did not influence the production of basidiomata.

O efeito dos fungos contaminantes Trichoderma sp. e Chaetomium olivacearum foi avaliado no cultivo dos isolados ABL 99/30 e ABL 04/49 de A. blazei, em duas formulações de composto, à base de palhas de tyfton (Cynodom dactylon) e aveia (Avena sativa). O delineamento experimental foi em esquema fatorial 2 x 2 x 3, inteiramente casualizado, com 6 repetições cada. A unidade experimental constou de 12 – 12,5 kg de composto úmido. Nos tratamentos envolvendo o Trichoderma sp. e o C. olivacearum durante a inoculação do A. blazei, foram adicionados 150 g de inóculo de cada um destes fungos contaminantes no momento da inoculação do A. blazei. O experimento foi conduzido em câmara climatizada, com umidade relativa entre 75-90% e temperatura média de 28 ºC. De acordo com os resultados obtidos, verificou-se que as médias de produtividade do isolado ABL 99/30 de A. blazei foram superiores às do isolado ABL 04/49; os fungos contaminantes C. olivacearum e Trichoderma sp. influenciaram negativamente na produção do A. blazei e os diferentes compostos (à base de palha de tyfton e aveia) não influenciaram na produção de basidiomas.
EFFECT OF CONTAMINANT ON THE PRODUCTIVITY OF TWO AGARICUS BLAZEI ISOLATES IN TWO COMPOST FORMULATIONS.
Keywords: Edible mushrooms; contaminants fungi; compost; Cogumelos; fungos contaminantes; isolados; composto